2015
DOI: 10.1007/s13204-015-0486-7
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using leaf extract of medicinally potent plant Saraca indica: a novel study

Abstract: Eco-friendly silver nanoparticles (AgNPs) have various applications in modern biotechnology for better outcomes and benefits to the society. In the present study, we report an eco-friendly synthesis of silver nanoparticles using Saraca indica leaf extract. Characterization of S. indica silver nanoparticles (SAgNPs) was carried out by Fourier transform infrared spectroscopy, scanning electron microscopy, energy dispersive spectrometry, Zeta potential, and transmission electron microscopy. SAgNPs showed antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Generally, appearance of brown color indicates the production of AgNPs due to SPR phenomenon. Similar indications were also reported [22,24]. Many studies reported that spherical AgNPs show maximum absorbance between 400 nm to 450 nm.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Generally, appearance of brown color indicates the production of AgNPs due to SPR phenomenon. Similar indications were also reported [22,24]. Many studies reported that spherical AgNPs show maximum absorbance between 400 nm to 450 nm.…”
Section: Discussionsupporting
confidence: 82%
“…It mainly showed the presence of carboxylic acids, esters, and steroids. They are reported to involve in the synthesis of nanoparticles [21,22]. It was previously reported that secondary metabolites present in endophytic fungi are responsible for synthesis and stabilization of AgNPs [8].…”
Section: Discussionmentioning
confidence: 99%
“…Ag-NPs have been obtained with sizes between 50 and 250 nm using Carica papaya leaf extract; 53 with average sizes 23±12, 32±24 and 19±22 nm using Illicium verum (star anise) seed extracts, 54 and average size 73 nm using an aqueous extract of Tephrosia tinctoria. 55 Regarding spherical shape homogeneity, our synthesis method was compared with that of other works where spherical Ag-NPs are synthesized, such as in the case of other green synthesis methods that employ leaf extracts of Saraca indica, 56 Ficus carica, 57 and Cocos nucifera. 58 The chemical and physical characterization of the Ag-NP samples suggests that the Acacia extract is capable of not only reducing the silver ions but also capping the Ag-NPs and stabilizing their surface.…”
Section: Discussion Synthesis and Characterization Of Ag-npsmentioning
confidence: 99%
“…41 42 The SPR band is highly sensible to the size and shape of the nanoparticles, which depend directly on the concentration of the extract and silver nitrate, and the type of biomolecules present in the plant extract. 43 Maximum absorption peaks at longer wavelengths suggest bigger sizes in the nanoparticles, on the other hand particles with smaller diameters interact with light at shorter wavelengths. 44 45 The characteristic SPR band, is due to the collective oscillation of the electrons located in the conduction band when they interact with light.…”
Section: Uv-vis Spectra Analysismentioning
confidence: 99%